2021
DOI: 10.1101/2021.02.08.21251362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 re-infection risk in Austria

Abstract: Background: A key question concerning coronavirus disease 2019 (COVID-19) is how effective and long lasting immunity against this disease is in individuals who were previously infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We aimed to evaluate the risk of SARS-CoV-2 re-infections in the general population in Austria. Methods: This is a retrospective observational study using national SARS-CoV-2 infection data from the Austrian epidemiological reporting system. As the primary outcom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
(60 reference statements)
1
23
0
1
Order By: Relevance
“…It is reasonable to expect that immunity acquired by natural infection provides effective protection against future infection with SARS-CoV-2. Observational studies have indeed found very low rates of reinfection over the following months among survivors of COVID-19 [6][7][8]. Reports of true reinfections are extremely rare in the absence of emergence of new variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to expect that immunity acquired by natural infection provides effective protection against future infection with SARS-CoV-2. Observational studies have indeed found very low rates of reinfection over the following months among survivors of COVID-19 [6][7][8]. Reports of true reinfections are extremely rare in the absence of emergence of new variants.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have found very low rates of reinfection among individuals with prior SARS-CoV-2 infection [6][7][8]. This brings up the question about whether it is necessary to vaccinate previously infected individuals.…”
mentioning
confidence: 99%
“…Recently, the issue of reinfection (SARS-CoV-2 subsequent infection after recovery from previous episode of the infection) and reactivation (also known as relapse, a re-detectable positive SARS-CoV-2 viral RNA in recovered patient which occurs within the first 4 weeks of previous infection) have been reported in several studies [see for instance (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and the references therein]. These studies highlighted the possibility of reactivation and reinfection of SARS-CoV-2 which needs urgent attention from the researchers as well the public health policymakers.…”
Section: Introductionmentioning
confidence: 99%
“…SIREN study which looks for answers to the questions about SARS-CoV-2 reinfection adds to other studies that the infection does protect against re-infection and possibly in an antibody-dependent manner [122] . Additionally, the findings indicate that infection and antibody response protects on par with or better than currently available SARS-CoV-2 vaccines [123] , [124] , [125] .…”
Section: Covid-19 Re-infectionmentioning
confidence: 88%